2023
DOI: 10.1159/000529134
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA BCAR4 Promotes Oxaliplatin Resistance in Colorectal Cancer by Modulating miR-484-3p/RAB5C Expression

Abstract: Background Oxaliplatin based chemotherapy resistance is a major cause of recurrence in patients with colorectal cancer (CRC). Increasing evidence indicates that LncRNA BCAR4 is involved in the occurrence and development of various cancers. However, the effect of BCAR4 on CRC chemotherapy resistance remains unclear. Methods Real-time quantitative PCR and western blotting were used to detect the expression levels of gene and protein, respectively. The role of BCAR4 in drug resistance was evaluated by cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The study by Li et al. reported that knocking down BCAR4 promotes apoptosis in CRC cells, which can be reversed by overexpressing RAB5C.The related regulatory axis is the BCAR4/miR-483-3p/RAB5C axis ( 76 ). Liu’s report indicates that silencing CASC9 can promote apoptosis by downregulating AKT3 expression through reducing the competitive binding of CASC9 with miR-576-5p ( 222 ).…”
Section: Lncrnas Regulate Cell Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Li et al. reported that knocking down BCAR4 promotes apoptosis in CRC cells, which can be reversed by overexpressing RAB5C.The related regulatory axis is the BCAR4/miR-483-3p/RAB5C axis ( 76 ). Liu’s report indicates that silencing CASC9 can promote apoptosis by downregulating AKT3 expression through reducing the competitive binding of CASC9 with miR-576-5p ( 222 ).…”
Section: Lncrnas Regulate Cell Apoptosismentioning
confidence: 99%
“…Li et al. reported that BCAR4 promotes oxaliplatin resistance by inhibiting apoptosis through the BCAR4/miR-483-3p/RAB5C axis ( 76 ). Liu found that CCAT1 enhances CRC cell resistance to oxaliplatin by transcriptionally activating CCAT1 through B-MYB, increasing SOCS3 promoter methylation to recruit DNMT1, thereby inhibiting SOCS3 expression and enhancing CRC cell resistance to oxaliplatin ( 82 ).…”
Section: Lncrnas Regulate Drug Resistancementioning
confidence: 99%